The Role of Social Media in Redefining Public Discourse in Nepal: A Political Perspective - Bhandari, Rita (Myagdi Guru, 2024)
This article aims to investigate the evolving landscape of the public sphere in the 21st century. Within the realms of media and communication studies, as well as public discourse. The term ‘social media’ has become ubiquitous, encompassing platforms such as Facebook, Twitter, YouTube, LinkedIn, Wordpress, Blogspot, Weibo, Pinterest, Foursquare, and Tumblr. The purpose of this paper is to understand how the concept of the public sphere contributes to a critical understanding of present society, advocating for an interpretation rooted in day to day activities of Nepalese people. For this information posted by 130 people from Facebook, and twitter have been collected from 31 July 5 September 2024 covering the common people, students, journalists, politicians and women. The perspective of Habermas is in favor of a political-economic foundation. The argument posits that a nuanced comprehension of Habermas’ original concept necessitates an immanent critical approach that scrutinizes the intersections of culture, media, and political economics, while also acknowledging power relations. The study establishes a theoretical framework for public service media, serving as the groundwork for identifying three areas of contention between the contemporary social media landscape and the realms of the state, the economy, and civil society. In conclusion, the article asserts that overcoming the situation at present requires a political stance to strengthen the people’s voices. It advocates for a transformation of social media and the internet into commons-based and public service media, thereby transcending existing limitations.